The response of provenance and family to drought stress at the progeny trial of Alstonia angustiloba - Mashudi; Liliana Baskorowati (Foresty Faculty of Hasanuddin University, 2016)
This experiment aimed to identify the provenance and family responses to drought stress of Alstoniaangustiloba Miq. progeny trial. This experiment was arranged in randomized complete block design. The research used 2 factors, i.e. provenance (Banten, Muara Enim, Musi Rawas and West Sumatera) and family (43 families). In this experiment, family factor was nested in the provenance. The results showed that the addition of the lowestmortality occurred in Banten provenance (9.22%) and highest in Muara Enim provenance (19.44%). A total of 36families had additional mortality in the range of 4.17 to 33.33%. Height and stem diameter increment of all provenances decreased due to drought stress, which ranged respectively from 0.02 to 0.27 m/year and 0.02 to 0.05 cm/year. Ranking of height increment did not change before and after the occurrence of drought stress, i.e.with the following order provenance of Muara Enim, Banten, Musi Rawas and Solok. In the family level, ranking of height and stem diameter increment before and after drought stress were vary slightly.